PERFORMANCE MEASUREMENT ANALYSIS OF CEMENT SACK WAREHOUSE USING BALANCED SCORECARD METHODS (A CASE STUDY OF PT SINAR TAMBANG ARTHALESTARI) - Faozanudin, Azalia Rizqya; Susanto, Novie (Program Studi Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2019)
Warehouse is recognized as an important facility for manufacturing companies. The purpose of warehouse may vary to each respective party that benefits from it. Because a huge amount of investment is poured over the existence of warehouse, these trigger the significance of performance measurement and assessment over the usage of warehouse. This paper deals with the application of Balanced Scorecard as a basis for creating indicators and metrics for warehouse performance's assessment, especially on the cements sacks warehouse in the respective company, PT Sinar Tambang Arthalestari. Experts' discussions presented that out of 4 perspectives of Balanced Scorecard, two are considered as the most important indicators to measure, which are costumer's perspective and internal business process' perspective. The customer's perspective indicator consists of quantity order fulfillment and quality order fulfillment, meanwhile the internal business process' is divided into space utility indicator and level stock control indicator. From the assessment's result, it showed that the warehouse is fairly-good operated. The details are, quantity order fulfillment for 40kgs is B-graded, 50kgs is C-graded; quality order fulfillment for 40kgs is A-graded and 50kgs is B-graded; space utility of warehouse is C-graded and level stock controls scored in D-graded. The result is further analyzed using 5WHY's analysis to find the basic cause of the performances. The analysis later explain that the poor performance of quantity order fulfillment indicators generated from the lack of schedule planning integration within the company, and the cause of performance on the space utility indicator is originated from the harbor authority. The poor performance of level stocks control issue is originally from the policy of company.